Geological Oceanography: Towards a Conceptual Framework - George Kontakiotis; Assimina Antonarakou; Dmitry A. Ruban (Journal of Marine Science and Engineering, 2022)
Research into modern oceans, seas, and their coastal zones, as well as marine ecosystems, provides valuable information for deciphering the geological dynamics [...]